PENGARUH MEDIA TIMBANGAN PINTAR TERHADAP KEMAMPUAN PENGUKURAN PADA ANAK USIA 5-6 TAHUN DI PAUD CENDANA KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Ratnawati Ratnawati; Zulkifli N; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations in the field it can be seen that the measurement ability of children aged 5-6 years is still in the category begins to develop. So it is necessary to use smart scales media. This study aims to determine the effect of smart scales media on measurement capabilities. This research was conducted at PAUD Cendana in the District of Rumbai Pesisir Pekanbaru City. This research used an experimental method with a pretest-posttest control group design with a sample of 30 children and use saturated sample techniques. Data collection techniques in this research are observation techniques. The data analysis technique used the t-test using the SPSS 22 program. The results of data analysis obtained t = 18.333 greater than t table = 2.048 with a significance of 0.000 <0.05. It can be concluded that there are differences in measurement abilities before and after the use of smart scales media. The influence given by the smart scales media based on the formula N Gain is 50.84%.Key Words: Measurement, Smart Scales